Loss of cerebellar glutamate transporters EAAT4 and GLAST differentially affects the spontaneous firing pattern and survival of Purkinje cells. (8th May 2018) - Perkins, Emma M; Clarkson, Yvonne L; Suminaite, Daumante; Lyndon, Alastair R; Tanaka, Kohichi; Rothstein, Jeffrey D; Skehel, Paul A; Wyllie, David J A; Jackson, Mandy
Abstract: Loss of excitatory amino acid transporters (EAATs) has been implicated in a number of human diseases including spinocerebellar ataxias, Alzhiemer's disease and motor neuron disease. EAAT4 and GLAST/EAAT1 are the two predominant EAATs responsible for maintaining low extracellular glutamate levels and preventing neurotoxicity in the cerebellum, the brain region essential for motor control. Here using genetically modified mice we identify new critical roles for EAAT4 and GLAST/EAAT1 as modulators of Purkinje cell (PC) spontaneous firing patterns. We show high EAAT4 levels, by limiting mGluR1 signalling, are essential in constraining inherently heterogeneous firing of zebrin-positive PCs. Moreover mGluR1 antagonists were found to restore regular spontaneous PC activity and motor behaviour in EAAT4 knockout mice. In contrast, GLAST/EAAT1 expression is required to sustain normal spontaneous simple spike activity in low EAAT4 expressing (zebrin-negative) PCs by restricting NMDA receptor activation. Blockade of NMDA receptor activity restores spontaneous activity in zebrin-negative PCs of GLAST knockout mice and furthermore alleviates motor deficits. In addition both transporters have differential effects on PC survival, with zebrin-negative PCs more vulnerable to loss of GLAST/EAAT1 and zebrin-positive PCs more vulnerable to loss of EAAT4. These findings reveal that glutamate transporter dysfunction through elevated extracellular glutamate and the aberrant activation of extrasynaptic receptors can disrupt cerebellar output by altering spontaneous PC firing. This expands our understanding of disease mechanisms in cerebellar ataxias and establishes EAATs as targets for restoring homeostasis in a variety of neurological diseases where altered cerebellar output is now thought to play a key role in pathogenesis.